Peran Guru dan Calon Pendidik Paud dalam Mengembangkan Kecerdasan Sosial Emosional Anak Usia Dini - Sulastya Ningsih; Mita Sari; Nunung Suryana Jamin; Annisa Fahmi Mannassai (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The development of early childhood social-emotional intelligence is an important aspect in the formation of character and social adaptability of children. This community service activity aims to enhance the understanding and competence of teachers and prospective PAUD educators through a national seminar that focuses on their strategic role in supporting children's social-emotional development. The implementation method is an interactive seminar involving expert speakers, group discussions, and practical case studies. The results of the activity showed a significant increase in participants' knowledge of the concept of social emotional intelligence, effective learning techniques, and strategies for managing children's emotions and positive social interactions. In addition, this seminar succeeded in encouraging teachers and prospective educators to apply a more empathetic and responsive learning approach to the emotional needs of early childhood. This activity makes a significant contribution to strengthening the role of educators as primary facilitators in the development of children's social-emotional intelligence, which ultimately supports the creation of a conducive and inclusive learning environment.